Chiral Ferrocenyl−Iodotriazoles and −Iodotriazoliums as Halogen Bond Donors. Synthesis, Solid State Analysis and Catalytic Properties. Issue 5 (27th January 2022) - Aubert, Emmanuel; Doudouh, Abdelatif; Wenger, Emmanuel; Sechi, Barbara; Peluso, Paola; Pale, Patrick; Mamane, Victor
Abstract: Despite the increasing number of applications based on halogen bond (XB), asymmetric catalysis purely based on such supramolecular interactions still remains a huge challenge. The first step toward its development is the design of appropriate XB chiral donor molecules with good catalytic properties. In this context, we report the synthesis of a series of iodinated compounds based on the triazole or triazolium ring and possessing the planar chirality of ferrocene. Their XB donor property was attested by X‐ray diffraction analysis, showing short I⋅⋅⋅N and I⋅⋅⋅F interactions in the triazole‐based derivatives and in the tetrafluoroborate salt of a idodotriazolium, respectively. The potential of these compounds to act as XB‐based catalysts was demonstrated in the aza‐Diels‐Alder reaction involving an imine and a diene. Whereas triazole‐based derivatives were inactive in this reaction, the triflate salts of iodotriazoliums delivered the expected cycloadduct with high yield. Abstract : Planar chiral ferrocenyl halogen‐bond donors with excellent catalytic properties are reported. Despite their propensity to form halogen‐bonds in the solid state, the ferrocenyl iodotriazole derivatives were inactive as catalysts. Alkylation of the triazole ring afforded triazolium salts where iodine σ‐hole depth was strongly increased, allowing efficient catalysis of an aza‐Diels‐Alder reaction through halogen‐bond activation of the imine.